Sympathetic neural reactivity to the Trier social stress test. (29th July 2022) - Bigalke, Jeremy A.; Greenlund, Ian M.; Nicevski, Jennifer R.; Tikkanen, Anne L.; Carter, Jason R.
Abstract : Abstract: Sympathetic responsiveness to laboratory mental stress is highly variable, making interpretations of its role in stress reactivity challenging. The present study assessed muscle sympathetic nerve activity (MSNA, microneurography) responsiveness to the Trier social stress test (TSST), which employs an anticipatory stress phase, followed by a public speaking and mental arithmetic task. We hypothesized that sympathetic reactivity to the anticipatory phase would offer a more uniform response between individuals due to elimination of confounds (i.e. respiratory changes, muscle movement, etc.) observed during more common stress tasks. Participants included 26 healthy adults (11 men, 15 women, age: 25 ± 6 years, body mass index: 24 ± 3 kg/m 2 ). Continuous heart rate (electrocardiogram) and beat‐to‐beat blood pressure (finger plethysmography) were recorded from all participants, while MSNA recordings were obtained in 20 participants. MSNA burst frequency was significantly reduced during anticipatory stress. During the speech, although burst frequency was unchanged, total MSNA was significantly increased. Changes in diastolic arterial pressure were predictive of changes in MSNA during anticipatory (β = −0.680, P  = 0.001), but not the speech ( P  = 0.318) or mental maths ( P  = 0.051) phases. Lastly, sympathetic reactivity to anticipatory stress was predictive of subsequent reactivity to both speech (β = 0.740, P  = 0.0002) and maths (β = 0.663, P  = 0.001). In conclusion, anticipatory social stress may offer a more versatile means of assessing sympathetic reactivity to mental stress in the absence of confounds and appears to predict reactivity to subsequent mental stress paradigms. Key points: Cardiovascular reactivity to laboratory mental stress is predictive of future health outcomes. However, reactivity of the sympathetic nervous system to mental stress is highly variable. The current study assessed peripheral muscle sympathetic nerve activity in response to the Trier social stress test, a psychosocial stressor that includes anticipatory stress, public speaking and mental arithmetic. Our findings demonstrate that sympathetic neural activity is consistently reduced during anticipatory stress. Conversely, the classically observed inter‐individual variability of sympathetic responsiveness was observed during speech and maths tasks. Additionally, sympathetic reactivity to the anticipatory period accurately predicted how an individual would respond to both speech and maths tasks, outlining the utility of anticipatory stress in future research surrounding stress reactivity. Utilization of the Trier social stress test in autonomic physiology may offer an alternative assessment of sympathetic responsiveness to stress with more consistent inter‐individual responsiveness and may be a useful tool for further investigation of stress reactivity. Abstract : Abstract figure legend Cardiovascular reactivity to laboratory mental stress is predictive of future health outcomes. The current study assessed peripheral muscle sympathetic nerve activity (MSNA) in response to the Trier social stress test, a psychosocial stressor that includes anticipatory stress, public speaking and mental arithmetic. Our findings demonstrate that MSNA was consistently reduced during anticipatory stress. Conversely, the classically observed inter‐individual variability of sympathetic responsiveness was observed during speech and maths tasks. Sympathetic reactivity to the anticipatory period accurately predicted how an individual would respond to both speech and maths tasks, outlining the utility of anticipatory stress in future research surrounding stress reactivity.